Informal networks in international business - Horak, Sven (Emerald Publishing Limited, 2022)
Informal networks can be a major obstacle to the effectiveness of managers. At the same time though, they can enable and facilitate business activities and support the efficiency and effectiveness of managerial actions. Since informal ties and networks can have a bright and a dark side, it is important for international managers to understand the way they work in the respective cultural context. Informal networks are often perceived as pervasive in emerging markets such as China or Russia, to be used to instrumentalize social capital and develop a relational competitive advantage or to simply circumvent formal rules. Contrary to this perception, they often stand for sociability and social cohesion, antecedents of a strong society. To date it remains unclear whether multinational enterprises have processes in place to identify, control, and manage informal ties and networks. Informal Networks in International Business sheds light into the complex nature of informal networks and the respective context in which they operate. Leading experts provide insights into novel research themes and extend conventional research paths on informal network phenomena in the international business context. The contributions in this edited volume help international business scholars, students, and international managers in globally operating organizations alike to develop knowledge about the dynamics, complexities and ambiguities of informal networks and informal networking worldwide.